2021
DOI: 10.2147/dmso.s271882
|View full text |Cite
|
Sign up to set email alerts
|

A Non-Invasive Prediction Model for Non-Alcoholic Fatty Liver Disease in Adults with Type 2 Diabetes Based on the Population of Northern Urumqi, China

Abstract: Background High prevalence of non-alcoholic fatty liver disease (NAFLD) occurs in type 2 diabetes mellitus (T2DM), and about 13% of diabetic patients eventually die of liver cirrhosis or liver cancer. The purpose of our research was to develop a non-invasive predictive model of NAFLD in adults with T2DM. Patients and Methods Adult patients diagnosed with T2DM during physical examination in 2018 in Urumqi were recruited, in total 40,921 cases. We chose questionnaire and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…These variables identified as risk factors for NAFLD are consistent with previous studies and are widely used in NAFLD risk scoring models. 23 , 26 , 27 In our prediction model, BMI is one of the main aspects of the NAFLD risk factor score. Numerous previous studies have confirmed obesity as a well-known risk factor for NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…These variables identified as risk factors for NAFLD are consistent with previous studies and are widely used in NAFLD risk scoring models. 23 , 26 , 27 In our prediction model, BMI is one of the main aspects of the NAFLD risk factor score. Numerous previous studies have confirmed obesity as a well-known risk factor for NAFLD.…”
Section: Discussionmentioning
confidence: 99%
“…The model displayed excellent discrimination and clinical value. Predictors in the model included BMI, FBG, TG, HDL, AST, ALT, Tbil, UA and monthly night shift, which contained some risk factors consistent with previous studies NAFLD [ 9 , 10 ]. and one factor reflecting the professional characteristics of nurses.…”
Section: Discussionmentioning
confidence: 93%
“…This may be the result of different department distributions, while only 7.65% of female nurses included in this study were working in emergency and critical care units. Furthermore, only females were recruited in this study, but males had been found to have a higher risk of NAFLD (OR 1.779, 95% CI 1.676–1.888) [ 9 ]. The participants included in this study were much younger than those in previous studies, while older age was an independent predictor of NAFLD occurance [ 9 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To meet this unmet need, we thus developed a novel predictive nomogram to determine NAFLD risk among pre-diabetic lean Chinese individuals with normal blood lipid levels. There have already been several predictive models developed to determine the risk of individuals ending up with T2DM and NAFLD, such as from Zhang et al and Xue et al [ 20 , 32 ], both of which focused on assessing NAFLD risk among Chinese T2DM. Another model from Cai et al [ 33 ] is able to estimate 8-year incidence of T2DM among NAFLD populations.…”
Section: Discussionmentioning
confidence: 99%